A Moment to Celebrate? Art of the Caribbean at the Venice Biennale. (1st April 2020) - Asquith, Wendy; Wainwright, Leon
In recent years, the sporadic presence of various Caribbean national pavilions at the Venice Biennale – Jamaica (2001), Haiti (2011), Bahamas (2013), Grenada (2015, 2017, 2019), Antigua and Barbuda (2017, 2019), Dominican Republic (2019) – has on each occasion been almost unanimously applauded as marking some sort of moment of 'arrival' or 'becoming' for artists of the Caribbean, and for the local institutional structures and professionals that surround them. This article critically explores what the gains are of such a presence beyond the fleeting 'Venice effect' – mega-hyped exposure to international audiences, curators, gallerists and other market actors. The alleged benefits-for-all of contemporary cultural exchange, in an expanding globalizing field such as Venice, are by no means shared equally, and such discourses gloss over layers of uneven privilege embedded within the institution.